The Servant Leadership for Non-Managers An Essential Handbook for Anyone Aspiring to Be a Leader - Kenneth Hunter (Great Britain ‎ Independently published, 2019)
If you are planning on becoming a respectable leader in the near future, and want the maximum competence from your team, then this is the type of leadership you need to learn.
References 152p.
Keywords: Leadership